Kampanye Brand Awareness Musik Lawas Indonesia - Farhan Hidayat; Neni Yulianita (Bandung Conference Series: Public Relations, 2022)
Abstract. This research, entitled Brand Awareness Campaign for Indonesian Old Music, conducted by the Alunan Nusantara Community discusses the campaign they carried out by bringing the issue of Indonesian old music to students who love it. The Alunan Nusantara Community is one of the old Indonesian music collectives from the 60s to 90s from the city of flowers who successfully spread their hobby by collecting cassette tapes and LPs or vinyl records of Indonesian music such as Chrisye, Fariz RM, Henry Manuputty, Rafika Duri, and many more again. Starting from a whim of looking for songs that don't exist on digital music platforms such as YouTube and Soundcloud, they are finally willing to drain their wallets by continuing to buy physical releases such as cassette tapes and LPs by Indonesian musicians. The purpose of this study was to find out why the Alunan Nusantara Community held a brand awareness campaign about Indonesian old music to students who love Alunan Nusantara music. This study uses a qualitative research method with a case study approach which is expected to be able to explore every uniqueness that exists in this research in depth and detail regarding the campaign activities carried out by the Alunan Nusantara Community. This study has three main results, namely a discussion of the steps taken by the Alunan Nusantara Community in carrying out their Brand Awareness campaign program, starting from the campaign planning process as a promotional and branding step that they do to attract the attention of their audience by looking for issues about music. old Indonesian music and in-depth exploration of old Indonesian music. Next, to find out why they are working on the old Indonesian music campaign, which is none other than to advance the repertoire of old music and as a step to preserve Indonesian old music by providing a forum for discussion for Indonesian old music lovers through the content of the offline and online events they work on. From that way, they also want to show their existence as a collective for preserving old Indonesian music from Bandung. Furthermore, to find out the process of implementing the Indonesian old music campaign that they carried out with various kinds of content, including: providing educational content about old Indonesian music through the Instagram social media platform, holding live spinning session events at several events in the city of Bandung, holding live radio streaming events by discussing thoroughly the topic of old Indonesian music, to releasing merchandise in the form of T-shirts and CD mixtape containing old Indonesian songs curated from the Alunan Nusantara Community itself. Abstrak. Penelitian dengan judul Kampanye Brand Awareness Musik Lawas Indonesia yang dilakukan oleh Komunitas Alunan Nusantara ini membahas tentang kampanye yang mereka lakukan dengan membawa isu musik lawas Indonesia kepada mahasiswa pecintanya. Komunitas Alunan Nusantara adalah salah satu kolektif musik Indonesia lawas era 60 sampai 90an asal kota kembang yang sukses menyebarluaskan hobinya dengan mengumpulkan kaset pita dan plat piringan hitam atau vinyl musik-musik nusantara seperti Chrisye, Fariz RM, Henry Manuputty, Rafika Duri, dan masih banyak lagi. Berawal dari keisengan mencari lagu-lagu yang tidak ada pada platform musik digital seperti YouTube dan Soundcloud, akhirnya mereka rela menguras isi dompetnya dengan terus membeli rilisan fisik seperti kaset pita dan piringan hitam karya musisi Indonesia. Tujuan dari penelitian ini adalah untuk mengetahui alasan Komunitas Alunan Nusantara mengadakan kampanye brand awareness perihal musik lawas Indonesia kepada kalangan mahasiswa pecinta musik Alunan Nusantara. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus yang diharapkan bisa mencari setiap keunikan yang ada pada penelitian kali ini secara mendalam dan teperinci mengenai kegiatan kampanye yang dilakukan oleh Komunitas Alunan Nusantara. Penelitian ini memiliki tiga hasil pokok pembahasan yaitu bahasan mengenai langkah-langlah Komunitas Alunan Nusantara dalam menjalankan program kampanye Brand Awareness yang mereka lakukan, mulai dari proses perencanaan kampanye sebagai langkah promosi dan branding yang mereka lakukan guna menarik perhatian para audinesnya dengan cara mencari isu mengenai musik lawas Indonesia dan ekslporasi mendalam mengenai musik lawas Indonesia. Selanjutnya guna mengetahui alasan mereka menggarap kampanye musik lawas Indonesia yang tidak lain dan tidak bukan untuk memajukan khasanah musik lawas dan sebagai langkah pelestarian musik lawas Indonesia dengan cara memberikan wadah diskusi untuk para pecinta musik lawas Indoenesia melalui konten acara offline maupun online yang mereka garap. Dari cara itu lah mereka juga ingin menunjukan eksistensi keberadaan mereka sebagai kolektif pelestarian musik lawas Indonesia asal Kota Bandung. Berikutnya guna mengetahui proses pelaksaan kampanye musik lawas Indonesia yang mereka lakukan dengan berbagai macam konten, diantaranya adalah: memberikan konten edukatif mengenai musik lawas Indonesia melalui plaform media sosial Instagram, mengadakan acara live spinning session pada beberapa acara di Kota Bandung, mengadakan acara live radio streaming dengan bahasan mengupas tuntas topik mengenai musik lawas Indonesia, hingga mengeluarkan merchandise berbentuk kaus dan CD mixtape berisikan lagu-lagu lawas Indonesia hasil kurasi dari Komunitas Alunan Nusantara sendiri.